2009
DOI: 10.1097/ccm.0b013e3181a55273
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of adenosine A2A receptor agonist in ventilator-induced lung injury in rats

Abstract: Objectives-Mechanical ventilation is associated with overwhelming inflammatory responses that are associated with ventilator-induced lung injury (VILI) in patients with acute respiratory distress syndrome. The activation of adenosine A 2A receptors has been reported to attenuate inflammatory cascades. Hypothesis-The administration of A 2A receptors agonist ameliorates VILI.Methods-Rats were subjected to hemorrhagic shock and resuscitation as a first hit to induce systemic inflammation. The animals randomly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…However, there is no clear consensus on the mechanisms whereby xanthines might influence inflammation. In contrast to our findings, a protective effect of adenosine A 2 receptor agonist has been observed in a mature rat lung injury model [20]. Li showed that chronic caffeine treatment at low dose and acute caffeine treatment at high dose attenuated lung damage and cytokine response in a mature mouse lung injury model, whereas acute caffeine treatment at low dose enhanced lung damage [21].…”
Section: Discussioncontrasting
confidence: 99%
“…However, there is no clear consensus on the mechanisms whereby xanthines might influence inflammation. In contrast to our findings, a protective effect of adenosine A 2 receptor agonist has been observed in a mature rat lung injury model [20]. Li showed that chronic caffeine treatment at low dose and acute caffeine treatment at high dose attenuated lung damage and cytokine response in a mature mouse lung injury model, whereas acute caffeine treatment at low dose enhanced lung damage [21].…”
Section: Discussioncontrasting
confidence: 99%
“…Generally speaking, mechanical ventilation is a lifesaving therapy as it improves hypoxemia and promotes alveolar opening in patients with acute respiratory failure; although, excessive alveolar distention as volutrauma and the cyclic opening and closing of lung units as atelectrauma may promote VILI [ 7 ]. Previous studies have shown that VILI alone may not cause extensive lung injury in the normal lung, but that VILI can enhance lung inflammation in pre-injured lungs [ 8 , 26 ]. This two-hit injury makes the lung more susceptible to mechanical ventilation injury, as there is increased pulmonary permeability, edema, neutrophil recruitment, and cytokine release into plasma [ 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A “two-hit injury” can be caused by VILI preceded by hemorrhagic shock and followed by reperfusion or acid aspiration, which makes the lung more susceptible to MV injury [ 8 , 9 ]. Although using a low tidal volume improves the clinical outcomes of certain populations of patients with ARDS, the mortality of ARDS patients remains high [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CGS-21680 Adenosine A2A receptor agonists 1. Adenosine A2A receptor agonists are reparative and anti-inflammatory in the lung following infection, acid, or mechanical injury [ 50 , 51 ] 5. RAGE Inhibitors RAGE neutralization 1.…”
Section: Therapies In Clinical Trials For Ardsmentioning
confidence: 99%
“…The adenosine A2A receptor agonist GW328267C enhanced alveolar fluid clearance in models of acid instillation, LPS, and live E.coli-induced lung injury [ 50 ]. Another adenosine A2A receptor agonist, CGS-21680, improved lung compliance and reduced neutrophil infiltration and pro-inflammatory cytokine release in a rat VILI model [ 51 ].…”
Section: Therapies In Clinical Trials For Ardsmentioning
confidence: 99%